2011
DOI: 10.1371/journal.pone.0026847
|View full text |Cite
|
Sign up to set email alerts
|

How Did the Spider Cross the River? Behavioral Adaptations for River-Bridging Webs in Caerostris darwini (Araneae: Araneidae)

Abstract: BackgroundInterspecific coevolution is well described, but we know significantly less about how multiple traits coevolve within a species, particularly between behavioral traits and biomechanical properties of animals' “extended phenotypes”. In orb weaving spiders, coevolution of spider behavior with ecological and physical traits of their webs is expected. Darwin's bark spider (Caerostris darwini) bridges large water bodies, building the largest known orb webs utilizing the toughest known silk. Here, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Recently there has been a renewed interest in the otherwise neglected area of spider neurophysiology with a number of anatomical studies on brain size and structure (Quesada et al, 2011;Park et al, 2013). Similar methods could be used to compare structures in the supraesophageal ganglion between spiders with extensive site exploration to spiders with hardly any, such as the Darwin's bark spider (Gregoric et al, 2011), in order to estimate the possible computational requirements of the behaviour. Even more promising is the potential of looking at the central nervous system of live spiders as they perform behaviours with new and more sophisticated electrophysiological and neuroimaging techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Recently there has been a renewed interest in the otherwise neglected area of spider neurophysiology with a number of anatomical studies on brain size and structure (Quesada et al, 2011;Park et al, 2013). Similar methods could be used to compare structures in the supraesophageal ganglion between spiders with extensive site exploration to spiders with hardly any, such as the Darwin's bark spider (Gregoric et al, 2011), in order to estimate the possible computational requirements of the behaviour. Even more promising is the potential of looking at the central nervous system of live spiders as they perform behaviours with new and more sophisticated electrophysiological and neuroimaging techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The assumption that radii construction (MA silk) comes at an energetic cost that is satisfied when adequate food or food of adequate energy/nutrient quality is consumed [15], [16], [19] partially explains these findings. Nonetheless, variations in radii number in spider orb webs are often correlated with variations in other architectural parameters, for example mesh size [11], [14], [15], [41]. We found that mesh size co-varied with radii number in A. aemula but not C. mulmeinensis as a response to variations in the concentration of protein consumed.…”
Section: Discussionmentioning
confidence: 65%
“…Several araneids (genera Eriophora and Caerostris ) spin orb-webs of extraordinary size and tensile strength suspended upon bridge lines of several meters, which led to the assumption that such web gigantism might have evolved as an adaptation for capturing flying vertebrates such as bats and birds [57][59]. In the case of Caerostris darwini , an araneid which spins giant orb-webs of up to 2 m diameter across rivers in Madagascar suspended upon bridge lines exceeding 20 meters in length, chiropterophagy could not be evidenced so far [58][59]. However, in this latter study the sample size of recorded predation events was rather small [58][59].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Caerostris darwini , an araneid which spins giant orb-webs of up to 2 m diameter across rivers in Madagascar suspended upon bridge lines exceeding 20 meters in length, chiropterophagy could not be evidenced so far [58][59]. However, in this latter study the sample size of recorded predation events was rather small [58][59]. In the habitats of Caerostris darwini , several species of small riverine bats of the families Vespertilionidae and Emballonuridae occur who would be available as potential prey at least for a few weeks per year during which time their volant juveniles (weighing ∼2.5–4 g) are within the spiders’ prey size range (S. Goodman, pers.…”
Section: Resultsmentioning
confidence: 99%